Cyclin D1 regulates osteoarthritis chondrocyte apoptosis via WNT3/β-catenin signalling. Issue 1 (4th December 2019) - Chen, Yi-Yue; Chen, You; Wang, Wan-Chuan; Tang, Qi-; Wu, Ren; Zhu, Wei-Hong; Li, Ding; Liao, Le-Le
Abstract: Objective: Cyclin D1 was an important molecular involved in the pathological process of osteoarthritis (OA). The purpose of this study was to identify the effect and potential mechanism of Cyclin D1 for the proliferation and apoptosis of OA chondrocytes. Methods: We used polymerase chain reaction (PCR) method to identify the expression levels of Cyclin D1 and down-stream Wnt/β-catenin pathway-related genes in OA chondrocytes according to the grade of OA. Small interfering RNA (siRNA) or overexpression of Cyclin D1 were used to identify the role of Cyclin D1 in cell proliferation and apoptosis. Next, we used XAV-939 to inhibit the Wnt/β-catenin pathway and explore the relevant mechanism. Results: Cyclin D1 was significantly decreased with OA grade ( p < .05). After siCyclin D1 transfection, the expression level of WNT3 and nuclear β-catenin were significantly increased, while Wnt10a and total β-catenin were not obviously changed. Co-cultured with XAV-939 and siCyclin D1 abolished the effects of siCyclin D1 on proliferation and apoptosis of OA chondrocytes ( p < .05). Conclusions: Cyclin D1 regulated chondrocyte proliferation and apoptosis through Wnt3/β-catenin instead of Wnt10a/β-catenin signalling pathway.